The Implementation of Sustainable Development to Achieve Climate Justice: Indonesian Perspective as an Archipelagic State - Wartini, Sri (Frontiers in Law, 2024)
Climate change causes serious impacts to the environment and to human beings. The impacts of climate change cannot be overcome by a single state, but it needs international cooperation. Each state has to act locally to participate in combating climate change in order to achieve climate justice. The research aims to analyze comprehensively the implementation of sustainable development to achieve climate justice Indonesian Perspective as an Archipelagic State. This study is a normative juridical research by applying conceptual and statutory approaches. The result of the research found that the policies strategies and efforts of Indonesian government to participate in achieving climate justice in the global spere still needs to be improved. However, there are some opportunities and challenges that have to be addressed. Thus, it is necessary to educate and to improve the public awareness to participate in the efforts of implementing sustainable development principle to achieve climate justice.